Online counseling using email: a qualitative study - Salleh, A.; Hamzah, R.; Nordin, N.; Ghavifekr, S.; Joorabchi, T.N. (2015)
Despite numerous studies in increasingly popular online mental health service, the nature of the relationship between online counselors and their clients, particularly in the email modality, deserves more attention. To enhance the knowledge in this area, this study was conducted to explore whether the online counseling relationship could be developed using email communication. Six qualified counselors and 59 clients volunteered to participate in the study. Using a qualitative approach, we collected data from two focus groups, individual interviews with participating counselors, 206 email interactions, and counselors' journals. To identify themes, we employed a grounded theory method. The emergent themes suggest that counselors describe the e-counseling relationship as having the following five features: initial establishment of a virtual relationship, structuring, text reinforcement, the development of a text relationship, and termination of the process. Each feature reflects a different level of relationship and different characteristics. Implications for future studies are also discussed.